2017
DOI: 10.1051/epjconf/201716005005
|View full text |Cite
|
Sign up to set email alerts
|

Isochrones of M67 with an Expanded Set of Parameters

Abstract: Abstract. We create isochrones of M67 using the Yale Rotating Stellar Evolution Code. In addition to metallicity, parameters that are traditionally held fixed, such as the mixing length parameter and initial helium abundance, also vary. The amount of convective overshoot is also changed in different sets of isochrones. Models are constructed both with and without diffusion. From the resulting isochrones that fit the cluster, the age range is between 3.6 and 4.8 Gyr and the distance is between 755 and 868 pc. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
3
2
0
Order By: Relevance
“…Michaud et al [192] argued that no CBM is required to reproduce the observed CMD of either M67 or NGC 188 if microscopic diffusion is included in the models. A similar conclusion for M67 was later found by Viani and Basu [193].…”
Section: Empirical Calibrations 41 Stellar Clusterssupporting
confidence: 89%
See 1 more Smart Citation
“…Michaud et al [192] argued that no CBM is required to reproduce the observed CMD of either M67 or NGC 188 if microscopic diffusion is included in the models. A similar conclusion for M67 was later found by Viani and Basu [193].…”
Section: Empirical Calibrations 41 Stellar Clusterssupporting
confidence: 89%
“…The sample in panel b was modeled using the Cesam2k code both with (open squares) and without (filled circles) microscopic diffusion, indicating that less CBM is needed to explain the observations if microscopic diffusion is taken into account [315]. This is in line with previous results from the open cluster M67 [192,193]. In comparison, the sample in panel c was modeled using the YREC code, using the concept of an effective overshoot parameter which accounts for the automatic adjustment of the size of the CBM region to avoid nonsensical core sizes [73].…”
Section: Extent Of the Cbm Region Across The Main-sequencesupporting
confidence: 86%
“…Previous studies have estimated the age of M67 to be within the range of 3.5-5.5 Gyr ( [13], [14], [15], [16], [17], [18]), in which our obtained value of 4.26 Gyr lies. One study [19] suggested that the Sun might have formed within a cluster sharing many of its properties (such as metallicity) with M67.…”
Section: Estimation Of Age Metallicity and Extinctionsupporting
confidence: 56%
“…Since gravitational settling in higher-mass models leads to the unobserved consequence of zero-metallicity atmospheres unless it is resisted by mass loss or radiative levitation (e.g., Deal et al 2018), the computation of which is computationally expensive, we tapered off diffusion for evolutionary tracks with M > 1.25 M according to the equation given by Viani & Basu (2017). Despite the unphysical nature of this prescription, the star under investigation here is of a low enough mass that the diffusion-tapered models are irrelevant.…”
Section: Effect Of Input Physicsmentioning
confidence: 99%